Survey of Student Knowledge About Medical and Non-Medical Waste Treatment: Survey Pengetahuan Mahasiswa Tentang Pengolahan Limbah Medis Dan Non Medis - Konradus Gregorius Ngete; Agusthinus Wali; Christina Ngadilah; Mery Novaria Pay (Poltekkes Kemenkes Kupang, 2020)
Knowledge is the result of remembering something, including recalling events that have been experienced either intentionally or unintentionally and this happens after people make contact or observe a certain object. Medical waste is waste originating from medical services, dental care, pharmacy, research, treatment, care or education that uses toxic, infectious, dangerous or dangerous materials unless certain safeguards are carried out. Non-medical waste is solid waste generated from non-medical hospital activities originating from kitchens, offices, and gardens from the yard that can be reused if there is technology. The purpose of this study was to determine the knowledge of students about medical and non-medical waste treatment at the Dental Nursing Department of the Health Polytechnic of the Kupang Ministry of Health. The type of research used is a descriptive type where this method will describe students' knowledge about the processing of medical waste and non-medical waste at the Dental Nursing Department Clinic, Poltekkes, Ministry of Health, Kupang. The results showed that the subject's knowledge of medical waste treatment at the Dental Nursing Department Clinic, Poltekkes Kemenkes Kupang was in the medium category (62.22%). The subject's knowledge of non-medical waste treatment at the Dental Nursing Department of the Health Poltekkes Kupang is in the good category (46.7%). The condition of medical and non-medical waste treatment at the Dental Nursing Department Clinic, Poltekkes, Kupang Ministry of Health is not up to standard or in poor category (35%). It is recommended that the clinic of the Department of Dental Nursing Poltekkes Kemenkes Kupang in order to further increase knowledge to students regarding the treatment of medical and non-medical waste, especially in the Clinic of the Department of Dental Nursing Poltekkes Kemenkes Kupang. Pengetahuan merupakan hasil mengingat suatu hal, termasuk mengingat kembali kejadian yang pernah dialami baik secara sengaja maupun tidak sengaja dan ini terjadi setelah orang melakukan kontak atau pengamatan suatu objek tertentu. Limbah medis adalah limbah yang berasal dari pelayanan medik, perawatan gigi, farmasi, penelitian, pengobatan, perawatan atau pendidikan yang menggunakan bahan-bahan beracun, infeksius, berbahaya atau membahayakan kecuali jika dilakukan pengamanan tertentu. Limbah non medis adalah limbah padat yang dihasilkan dari kegiatan rumah sakit diluar medis yang berasal dari dapur, perkantoran, serta taman dari halaman yang dapat dimanfaatkan kembali apabila ada teknologi. Tujuan penelitian ini adalah untuk mengetahui pengetahuan mahasiswa tentang pengolahan limbah medis dan non medis di Klinik Jurusan Keperawatan Gigi Poltekes Kemenkes Kupang. Jenis penelitian yang digunakan adalah jenis penelitian deskriptif dimana metode ini akan menggambarkan pengetahuan mahasiswa tentang pengolahan limbah medis dan limbah non medis di Klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang. Hasil penelitian menunjukkan bahwa pengetahuan subjek tentang pengolahan limbah medis di Klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang termasuk kategori sedang (62,22%). Pengetahuan subjek tentang pengolahan limbah non medis di Klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang termasuk kategori baik (46,7%). Kondisi pengolahan limbah medis dan non medis di Klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang belum sesuai standar atau kategori buruk (35%). Disarankan agar klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang agar lebih meningkatkan pengetahuan kepada mahasiswa mengenai pengolahan limbah medis dan non medis terkhususnya di Klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Kupang.